EXPLORING GLOBAL TRENDS AND FUTURE PROSPECTS IN FISHING TECHNOLOGY RESEARCH: AN INNOVATIVE BIBLIOMETRIC APPROACH - Riska Fatmawati; Jhonnerie, Romie; Hendrizal, Andri; Siagian, Desi Rahmadani (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
Fishing technology has undergone rapid development in response to sustainability challenges; however, a comprehensive global synthesis of its research progress and future directions remains lacking. To address this gap, this study explores global trends and prospects in fishing technology research using an innovative bibliometric approach. A total of 164 Scopus-indexed documents published between 2009 and 2023, authored by 179 researchers across 33 countries, were analyzed. Bibliometric analysis was conducted using the Biblioshiny application in the Bibliometrix R package, complemented by knowledge domain visualization (KDV) to map scientific structures, collaboration networks, and citation patterns. The results indicate an annual publication growth rate of 12.3%, reflecting increasing global interest in fishing technology. China was identified as the most productive country, with the strongest record of international collaboration, while Cooke SJ emerged as the most influential scholar, with a PageRank score of 0.0204 and accounting for 18.25% of global citations. Keyword mapping revealed research hotspots centered on sustainable development, selective fishing gear, and the integration of digital technologies, including artificial intelligence and electronic monitoring. This study concludes that bibliometric synthesis not only provides a strategic overview of global knowledge gaps and thematic evolution but also highlights the critical role of interdisciplinary collaboration and technological innovation in shaping the future of sustainable fisheries management. Keywords:   Bibliometrics analysis, fisheries, fishing technology